Plan de manejo turístico para la ciudad de Bahía de Caráquez – provincia de Manabí. - Pérez Loor, María Alejandra (2013)
In developing this thesis presents a tourism management plan for natural and cultural resource for the city Caráquez Bay - Manabí Province, which has enabled us to diagnose the current situation of the study area, for it was necessary to use techniques and information gathering tools such as interviews, document review, direct observation, surveys, group work, among others that will be detailed below. This research has 5 chapters, within which contains the following: Chapter I projected the background, approach and the formulation of the research problem, the rationale, aims and objectives, and to defend the idea. Likewise in Chapter II covers everything related to theoretical concepts concerning the delimiting management plan, followed by Chapter III refers to the methodology used in developing this thesis research which is directed to the City of Bay Caraquez through the tourism management plan. Chapter IV describes the results of the research project, which date through a situational analysis tourist city previously said that is involved in the investigation, as the development consist of natural and cultural inventories of such city, the determination of the critical areas, limitations, problems and strengths of the city through a SWOT and program design and consistent actions to achieve the desired location in the city of Bahia. Chapter V is based on the wording of the conclusions and recommendations, as well as the bibliography and the development of evidence projecting thesis research.